Paraseptal Emphysema: Prevalence and Distribution on CT and Association with Interstitial Lung Abnormalities - Araki, Tetsuro (Eur J Radiol, 2015)
OBJECTIVE: To investigate the prevalence and distribution of paraseptal emphysema on chest CT images in the Framingham Heart Study (FHS) population, and assess its impact on pulmonary function. Also pursued was the association with interstitial lung abnormalities. MATERIALS AND METHODS: We assessed 2633 participants in the FHS for paraseptal emphysema on chest CT. Characteristics of participants, including age, sex, smoking status, clinical symptoms, and results of pulmonary function tests, were compared between those with and without paraseptal emphysema. The association between paraseptal emphysema and interstitial lung abnormalities was investigated. RESULTS: Of the 2633 participants, 86 (3%) had pure paraseptal emphysema (defined as paraseptal emphysema with no other subtypes of emphysema other than paraseptal emphysema or a very few centrilobular emphysema involved) in at least one lung zone. The upper zone of the lungs was almost always involved. Compared to the participants without paraseptal emphysema, those with pure paraseptal emphysema were significantly older, and were more frequently male and smokers (mean 64 years, 71% male, mean 36 pack-years, p<0.001) and had significantly decreased FEV(1)/FVC% (p=0.002), and diffusion capacity of carbon monoxide (DLCO) (p=0.002). There was a significant association between pure paraseptal emphysema and interstitial lung abnormalities (p<0.001). CONCLUSIONS: The prevalence of pure paraseptal emphysema was 3% in the FHS population, predominantly affects the upper lung zone, and contributes to decreased pulmonary function. Cigarette smoking, aging, and male gender were the factors associated with the presence of paraseptal emphysema. Significant association between paraseptal emphysema and interstitial lung abnormalities was observed.